Dilute Russell viper venom time interpretation and clinical correlation: A two‐year retrospective institutional review. (8th September 2018) - Jacquot, Cyril; Wool, Geoffrey D.; Kogan, Scott C.
Abstract: Introduction: The dilute Russell viper venom time (dRVVT) detects lupus anticoagulant (LA). International Society for Thrombosis and Haemostasis (ISTH) guidelines specify positivity criteria, which differ from the assay manufacturer's criteria. Methods: Two years of dRVVT testing at our institution were reviewed. For patients with prolonged dRVVT screening times, we evaluated dRVVT results by ISTH and manufacturer's criteria and correlated with the results of other antiphospholipid syndrome (APS) testing (LA‐sensitive activated partial thromboplastin time and antiphospholipid antibodies) and with history of thromboembolism and other APS manifestations. Results: Approximately one‐fifth of dRVVTs exhibited a prolonged screening time. Among first prolonged dRVVTs, 35% were positive by both ISTH and manufacturer criteria, 44% met neither criteria, and 20% were equivocal (positive by only ISTH or manufacturer). Positivity by ISTH guidelines alone correlated better with other positive APS tests than manufacturer criteria positivity. Positive dRVVTs by both criteria correlated even more strongly with other positive APS assays. We investigated the likelihood of eventual APS diagnosis depending on the testing indication. No patient tested for LA solely for prolonged screening aPTT was subsequently diagnosed with APS. In patients with thrombosis, prolonged dRVVT clotting time not meeting both ISTH and manufacturer criteria was rarely associated with eventual APS diagnosis. Conclusion: We examined the correlation of dRVVT results with other APS testing and clinical outcomes. Interpretation method impacted how dRVVT results related to other APS testing, and, in limited data, to clinical findings. Patients with prolonged dRVVTs meeting only one set of positivity criteria rarely received an APS diagnosis.